Customer Perception Towards Brand: A Study on aPatanjalia (Global Journal of Management and Business Research, 2015)
Introduction-The ever changing marketing scenario and heightened competition over the globe has amplified the role of brand at unparalleled level. Every person is a consumer of different brands at the same time. The choice and usage of a particular brand by the consumer over the time is affected by the quality benefits offered by the brand especially when it comes to brand of eatables and cosmetics. Consumer satisfaction is derived when he compares the actual performance of the product with the performance he expected out of the usage. Philip Kotler (2008) observed that satisfaction is a person's feelings of pressure or disappointment resulting from product's perceived performance (outcome) in relation to his or her expectations. If the perceived benefits turned out to be almost same as expected, customer is highly satisfied and that is how the company achieves loyalty of the customer towards the products.
Keywords: changing marketing scenario and heightened competition